Advancements of MOFs in the Field of Propane Oxidative Dehydrogenation for Propylene Production - Shu-Ting Li; Ming Ke; Jie Zhang; Yun-Lei Peng; Guangjin Chen (Molecules, 2024)
Compared to the currently widely used propane dehydrogenation process for propylene production, propane oxidative dehydrogenation (ODHP) offers the advantage of no thermodynamic limitations and lower energy consumption. However, a major challenge in ODHP is the occurrence of undesired over-oxidation reactions of propylene, which reduce selectivity and hinder industrialization. MOFs possess a large number of metal sites that can serve as catalytic centers, which facilitates the easier access of reactants to the catalytic centers for reaction. Additionally, their flexible framework structure allows for easier adjustment of their pores compared to metal oxides and molecular sieves, which is advantageous for the diffusion of products within the framework. This property reduces the likelihood of prolonged contact between the generated propylene and the catalytic centers, thus minimizing the possibility of over-oxidation. The research on MOF catalyzed oxidative dehydrogenation of propane (ODHP) mainly focuses on the catalytic properties of MOFs with cobalt oxygen sites and boron oxygen sites. The advantages of cobalt oxygen site MOFs include significantly reduced energy consumption, enabling catalytic reactions at temperatures of 230 °C and below, while boron oxygen site MOFs exhibit high conversion rates and selectivity, albeit requiring higher temperatures. The explicit structure of MOFs facilitates the mechanistic study of these sites, enabling further optimization of catalysts. This paper provides an overview of the recent progress in utilizing MOFs as catalysts for ODHP and explores how they promote progress in ODHP catalysis. Finally, the challenges and future prospects of MOFs in the field of ODHP reactions are discussed.